Transcriptomic correlates of cell cycle checkpoints with distinct prognosis, molecular characteristics, immunological regulation, and therapeutic response in colorectal adenocarcinoma - Wang, Heng; Wang, Wei; Wang, Zhen; Li, Xu (Frontiers in Immunology, 2023)
Backgrounds: Colorectal adenocarcinoma (COAD) is a kind of malignant digestive tumor. Some cell cycle checkpoints (CCCs) have been found to contribute to CRC progression, whereas, the integrated role of checkpoint mechanism in cell cycle, remain unclear. Materials and Methods: The GDC TCGA COAD cohort was retrieved as the training dataset. A total of 209 CCC related genes were derived from Gene Ontology Consortium, and were subsequently enrolled into the univariate, multivariate, and least absolute shrinkage and selection operator (LASSO) Cox regression analyses. Cell proliferation and Transwell assay analyses were utilized to evaluate the functional roles of signature-related CCCs. Underlying CCCs signature, molecular characteristics, immune-related features, and therapeutic response were finally estimated. Results: Univariate Cox regression analysis identified 27 CCC related genes significantly affecting overall survival (OS) of COAD patients, subsequently, LASSO analysis determined a novel CCCs signature. Noticeably, CDK5RAP2, MAD1L1, NBN, RGCC, and ZNF207 were first identified to be correlated with the prognosis of COAD, and it was proved that all of them were significantly correlated with the proliferation and invasion of HCT116 and SW480 cells. In TCGA COAD cohort, CCCs signature robustly stratified COAD patients into high and low CCCs score groups, with the good AUC values for OS prediction at 1-, 2-, and 3-years were 0.74, 0.78, and 0.77. Furthermore, CCCs signature was independent from clinical features. Intriguingly, functional enrichment analysis confirmed CCCs score was markedly associated with the extracellular matrix & immune (chemokine) related signaling, cell cycle related signaling, and metabolisms. Impressively, higher CCCs score was positively correlated with a majority of chemokines, receptors, immunostimulators, and anti-cancer immunity, indicating a relatively immune-promoting microenvironment. Eventually, GDSC database analysis showed that lower CCCs score were likely to be more sensitive to 5-fluorouracil, bosutinib, gemcitabine, gefitinib, methotrexate, mitomycin C, and temozolomide; while patients with higher CCCs score seemed to have the higher level of sensitivity to bortezomib and elesclomol. Conclusions: The novel CCCs signature exhibited good ability of prognosis prediction, and CCCs score was found to be highly correlated with molecular features, immune-related characteristics, and therapeutic responses, which would greatly promote the clinical management and precision medicine for COAD.